Macroeconomic Management for Poverty Reduction : Chad, Mali, Niger - World Bank Group (World Bank, Washington, DC, 2018)
Macroeconomic management in Chad, Mali and Niger needs to account for a number of specific parameters. Very rapid population growth exerts immense pressure on the demand for education and health services. Economic activity and prices are strongly influenced by climatic variations, and exports and government revenues depend on a few commodities whose price widely fluctuate. Security threats complicate budget planning and divert public resource from developmental uses. Belonging to monetary unions strengthens macroeconomic stability, but limits as well the range of policy instruments at the disposal of countries' authorities to address the many developmental challenges they face.